PENGELOLAAN SARANA DAN PRASARANA KAWASAN WISATA PANTAI IMPOS DESA MEDANA KECAMATAN TANJUNG KABUPATEN LOMBOK UTARA - Lalu Juliyadi; Lalu Masyhudi; I Nyoman Tri Sutaguna (Sekolah Tinggi Pariwisata Mataram, 2022)
Impos Beach is one of the tourist destinations in Karang Anyar Hamlet, Medana Village, Tanjung District, North Lombok Regency, West Nusa Tenggara Province. This study aims to determine the availability of facilities and infrastructure and to describe the management of facilities and infrastructure for the Impos Beach Tourism Area, Medana Village, Tanjung District, North Lombok Regency. This study used descriptive qualitative method. The method of determining respondents was purposive sampling. The data used in this study were observation, interviews and documentation. The data analysis used is descriptive qualitative analysis, namely to reveal events or facts, circumstances, phenomena, variables and circumstances that occurred during the research by revealing what actually happened. The results of this study are the availability of facilities and infrastructure for the Impos Beach Tourism area is quite good but there are some that need to be added because they are not in accordance with the number of visits. Impos Beach is managed by Pokdarwis Sejahtera Pantai Impos which has been running since 2017 until now. The management of the facilities and infrastructure of the Impos Beach Tourism Area is still not optimal due to the lack of public awareness in protecting the environment on the Impos Beach and the lack of cohesiveness from Pokdarwis members because they are more concerned with private stalls.